Literature Review: Implementation of a Differentiated Problem-Based Learning Model to Improve Mathematical Literacy - Selpiana Selpiana; Alim Bahri Mahmul; Asdar Asdar (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2026)
Mathematical literacy is an essential competence in mathematics education; however, numerous studies indicate that students’ mathematical literacy in Indonesia remains at a low to moderate level. This study aims to systematically examine the condition and challenges of students’ mathematical literacy in Indonesia, the factors contributing to low mathematical literacy in conventional instruction, the implementation of Problem-Based Learning (PBL) integrated with differentiated instruction as a learning solution, as well as the strengths and limitations of applying differentiated PBL in mathematics learning. This study employed a literature review method by analyzing 21 relevant scientific articles published between 2023 and 2025. Data were analyzed using a qualitative descriptive approach through the classification and synthesis of research findings based on four analytical focuses. The findings reveal that low mathematical literacy is characterized by students’ difficulties in understanding contextual problems, modeling mathematical situations, and interpreting solutions. The main contributing factors include teacher-centered instruction, the dominance of procedural exercises, limited real-world contexts, and the lack of accommodation for students’ diverse characteristics. The implementation of differentiated PBL has been shown to effectively improve mathematical literacy and its supporting skills, although challenges remain in terms of lesson planning, time allocation, teacher readiness, and authentic assessment.